The effects of pity on self- and other-perceptions of mental illness. (30th July 2016) - Fominaya, Adam W.; Corrigan, Patrick W.; Rüsch, Nicolas
Abstract: Previous research has demonstrated that pity may have a positive influence on public perceptions of individuals with a mental illness but has not adequately addressed the potential negative impacts of pity perceptions. Seventy-five research participants with serious mental illness completed measures of pity, public stigma, shame, hopelessness, personal empowerment, self-esteem, depression, and quality of life at baseline. Measures of hopelessness, personal empowerment, self-esteem, and depression were repeated six months later. Bivariate correlations found significant associations between pity and "other" effects of stigma including dangerousness, fear, segregation, avoidance and perceived stigma. Baseline pity was significantly correlated with self-effects of stigma such as shame, hopelessness, lower empowerment, lower self-esteem, depression, and decreased quality of life. At six-month follow-up, baseline pity was still associated with increased hopelessness and depression along with decreased empowerment and self-esteem. Anger, avoidance, perceived stigma, shame, and self-esteem were significantly related to pity in multiple linear regressions. Outcomes of path analyses suggest that the significant positive relationship between pity at baseline and depression at six-month follow-up was mediated by self-esteem and hopelessness. Individuals who view mental illness with pity experience negative self- and other-effects of stigma. These effects persist 6-months later. These findings have important implications for stigma-reducing advertising programs. Highlights: Seventy-five subjects with mental illness provided data at baseline and follow-up. We explored the relationship between pity and depression 6-months later. A structural equation model (SEM) was used to test mediating relationships. Self-esteem and hopelessness mediated the relationship between pity and depression. Negative effects of pity were demonstrated at 6-month follow-up.